Edukasi Pencegahan Pre Eklampsia dan Determinan Post Partum Blues untuk Kesehatan Ibu dan Anak - Liliek Pratiwi; Uus Husni Mahmud; Ito Wardin; Harnanik Nawangsari; Maharnani Tri Puspitasari (Lembaga Pengembangan Kinerja Dosen, 2024)
According to the Indonesian Health Profile (2021), preeclampsia or eclampsia, bleeding, and COVID-19 caused the highest number of maternal deaths in 2021. In 2022, the maternal mortality rate in Indonesia reached 183 deaths per 100,000 live births, with preeclampsia as the main cause. One of the most common maternal health problems in Indonesia is preeclampsia, which has a high incidence rate and causes dangerous complications for both mother and baby. Research and prevention efforts continue to be needed to reduce maternal mortality in Indonesia. In addition to disorders during pregnancy, we as academics who continue to be pro-active in community service activities in our fields, must also pay attention to postpartum health. The incidence rate of postpartum blues in Indonesia will reach 50-70% in 2023. According to the WHO, around 10% of pregnant women and 13% of new mothers experience mental health disorders, especially depression. Risk factors that increase the likelihood of postpartum blues are the young age of the mother, lack of support from the husband, and difficult economic situation. The method used in this activity is lectures and discussions, with power point and leaflet media. Target Women of Childbearing Age (WUS), pregnant women and postpartum mothers. After the educational activity, participants asked several questions, such as how to know if a pregnant woman has a disorder, how many times to do a check-up, and what the family should do if the mother seems stressed after childbirth.